O processo de trabalho dos avicultores parceiros da Sadia S.A: controles, mediações e autonomia - Zen, Rosane Toebe (2009)
This research was originally designed to understand the training for the work of poultry farmers, subject responsible for the production of raw chicken in the poultry industry. Upon finding that the learning activity is the pursuit of work, with the formal training for work, the search was scaled, and the “work process of the poultry assumed the centrality of research”. The completion of the research involved the use of primary and secondary sources, and the first consisted in the application of questionnaires, visits to the properties and analysis of documents requested to poultry farmers. The secondary sources were raised by means of literature search. The study shows that the marks of contemporary capitalism are present in the poultry industry: an eminent political participation and economic development in the state sector, production restructuring and heterogeneity in the composition of the collective worker in the production process. In general, this study identified the limits and possibilities of the poultry farmers to exercise control over the process of their work. Poultry industry and poultry farmers establish a relationship in which the first exerts strong control over them. The control is through technical assistance, the completion of forms and information are provided to industry through phone calls. Although the control of agribusiness over the entire production process is paramount, there are situations where such control eludes him, because between the guidelines and charges of the company and the daily act of poultry farmers are in the areas of mediation, which are operated by poultry farmers to in opportunity, act independently in the production process. While exercising some autonomy, it is aiming to achieve better production results, which focus directly on their income. Thus, the gain of the industrial capital on the work of poultry farmers case even in the spaces of autonomy that these subjects earn in the production process. This study shows that the poultry farmers, while the control question as subject, not demanding more autonomy in the workplace: in essence, their disputes with the industry revolve around the search for greater returns in economic activity.